Analisis Penggunaan Metode Cooperative Integrated Reading And Composition Dalam Meningkatkan Hasil Belajar Aqidah Di SMP Al-Mukmin Benteng Hilir - Irfan Fiddin (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2025)
The purpose of this research is to enhance students' understanding of learning and comprehension of Aqidah for eighth-grade students at SMP Al Mukmin, through an approach using the Cooperative Integrated Reading and Composition (CIRC) method.This research uses the Classroom Action Research (CAR) method.The research results show that there is a significant increase in the learning outcomes of aqidah with the application of the Cooperative Integrated Reading and Composition learning model steps.In cycle I, when data was collected, the Cooperative Integrated Reading and Composition learning model had not yet been applied, and students' learning outcomes were still quite low, as indicated by their learning achievement scores.Then, when the Cooperative Integrated Reading and Composition learning model was implemented, student learning outcomes improved to 57.5% in Cycle I with an average score of 72.02%.In Cycle II, after using the Cooperative Integrated Reading and Composition learning model, it showed an average result of 85.0%.This shows a significant increase of 12.98%.